AN INTRODUCTION TO FUNCTIONAL GRAMMAR (Third Edition) & AN EXPERIENTIAL GRAMMAR OF THE VIETNAMESE CLAUSE - Lan, Nguyen Thuy Phuong (VNU Journal of Foreign Studies; Vol 34 No 5DO - 10.25073/2525-2445/vnufs.4314, 2018)
AN INTRODUCTION TO FUNCTIONAL GRAMMAR  (Third Edition) M.A.K. Halliday & Christian M.I.M. Matthiessen London: Edward Arnold, 2004/2014   AN EXPERIENTIAL GRAMMAR OF THE VIETNAMESE CLAUSE Hoang Van Van  Hanoi: Education Publishing House, 2012